Policy for Prevention of a Retained Sponge after Vaginal Delivery - David J. Garry; Sandra Asanjarani; Donna M. Geiss (Case Reports in Medicine)
Background. Policies for sponge count are not routine practice in most labor and delivery rooms. Ignored or hidden retained vaginal foreign bodies has potentially significant health care morbidity. Case. This was a case of a retained vaginal sponge following an uncomplicated spontaneous vaginal delivery. Delivery room policy resulted in the discovery of the sponge on X-ray when an incorrect sponge count occurred and physical exam did not find the sponge. Conclusion. This emphasizes the use of protocols to enhance patient safety and prevent medical error.